Study of Cultural Public Events in the Field of Culture and Art (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article talks about the history of the emergence of cultural and mass events and their impact on our social and cultural life. Aspects related to cultural events are analyzed in cultural studies and art history.